Simulações ópticas para o comissionamento da linha de luz SAPUCAIA - Souza, Bruno Santos de (Universidade Federal de São Carlos, 2024)
The SAPUCAIA beamline is one of the research stations at the Brazilian Synchrotron Light Laboratory (LNLS) and is in the final stages of installation. It will employ the small-angle X-ray scattering technique to characterize the structure and morphology of nano- and microstructured materials, operating in the energy range of 5 to 18 keV. The planned photon source for SAPUCAIA is a KYMA undulator. However, the KYMA undulator will only be available in the first semester of the next year, leading to the decision to perform the initial commissioning – a process to prepare the beamline for operation – using the PAPU undulator, a device built by researchers at CNPEM. The modification of the undulator has significant implications for beam characteristics (size, divergence, flux), and studies need to be conducted to enable the proper commissioning of the beamline. This work aims to conduct these studies through optical simulations to support and optimize the commissioning process of the SAPUCAIA beamline with the PAPU undulator. Specifically, efforts were made to identify beam properties such as size, shape, and position at each Beam Position Monitors (BPM), using specialized programs including SHADOW, SRW, and SPECTRA. Through simulations, it was possible to analyze the beam behavior along the beamline, calculate the line resolution as 1.56×10−4, and map the effects of misalignments on the single mirror of the beamline. Additionally, not only were the focus positions and depth of focus determined, but also the beam movement rates. The set of information obtained contributes to and optimizes the beamline commissioning time.
Optical simulations for commissioning the SAPUCAIA beamline
Keywords: Fonte de Luz Síncrotron; Sirius; Comissionamento de linha de luz; SAPUCAIA; Simulações ópticas; Synchrotron Light Source; Beamline commissioning; Optical simulations; CIENCIAS EXATAS E DA TERRA::FISICA::AREAS CLASSICAS DE FENOMENOLOGIA E SUAS APLICACOES::OTICA